Pola Kemitraan antara Petani Melon dengan CV Agrowates dalam Meningkatkan Pendapatan - Tri Kurniastuti (Flora : Jurnal Kajian Ilmu Pertanian dan Perkebunan, 2025)
This study aims to determine the partnership pattern between CV Agrowates and melon farmers and to determine the difference in income of melon farmers before and after partnering. The research design used in this research is descriptive qualitative and quantitative analysis methods with survey research methods, sampling using saturated sampling To determine the income of farmers before and after partnering used cost analysis and farm income (profit), namely Profit (p) = Total Revenue (TR) - Total Cost (TC). To determine the difference in income of melon farmers before and after the partnership was further analyzed with the T-test. The results showed that the partnership pattern between the CV Agrowates company was the Agribusiness Operational Cooperation (KOA) partnership pattern. The role of partner farmers as providers of land, labor, production equipment and production facilities such as fertilizers, while the company as a means of providing seeds, extension and guidance of cultivation personnel. The partnership pattern significantly shows a real difference. Income before partnering amounted to Rp. 116,259,299.93 with R / C of 2.95 while the income of farmers after partnering amounted to 146,612,513.3 with R / C of 3.37, Partnership can increase the income of melon farmers in Wates Village by 26.11%.